A simple test for alternative states in ecological restoration: the use of principal response curves. Issue 2 (15th July 2013) - Alday, Josu G.; Marrs, Rob H.; Walker, Lawrence
Abstract Aims Ecological resistance and resilience and its link to alternative states is an important concept in ecological restoration. In many situations there is a need to flip one ecosystem state to another and then keep it there; thus there is a need to overcome the resistance/resilience of the starting community and create another one with sufficient resistance/resilience to maintain it in that state. The difficulty for ecological restoration is that these concepts are complicated to measure in practice, and hence tend to be discussed in rather abstract terms. Here, we describe the application of principal response curves (PRC) to test for the creation of alternative states or alternative stable states in ecological restoration studies. Location Six experiments on acid grassland and heathland invaded by Pteridium aquilinum across Great Britain. Methods We use PRC, a multivariate approach, to measure change in ecological restoration experiments that allows a formal test of whether alternative states are created. We used PRC to test for change in plant species composition in a series of replicated experiments designed to change a late‐successional ecosystem, dominated by P. aquilinum, into either heathland or acid grassland. Here, we tested three Pteridium control treatments, including two 'one‐off' treatments (applied only at the start) and a 'repeated' (applied regularly) treatment, against an untreated experimental control. Results In the heathland targets, alternative states were induced within 10 yrs using the 'repeated' treatment (cutting twice per year). All 'one‐off' treatments either did not overcome the resistance of the starting community or if they did, produced a temporary displacement, but the resilience of the initial state was too high and there was a rapid reversion to the starting community. In the grassland community, alternative states were induced by 'repeated' treatment (cutting twice per year), but the 'one‐off' treatment suggested creation of an alternative stable state that lasted 10 yrs. Conclusions For the first time, there is a methodology using PRC that tests for the creation of alternative states or alternative stable states in ecological restoration research. The drawback is that a long‐term data set from replicated experiments with an untreated control treatment is needed.